2022
DOI: 10.3390/biologics2030015
|View full text |Cite
|
Sign up to set email alerts
|

Changes in SpO2 on Room Air for 34 Severe COVID-19 Patients after Ivermectin-Based Combination Treatment: 62% Normalization within 24 Hours

Abstract: The emergence of COVID-19 in March 2020 challenged Zimbabwe to respond with limited medical facilities and therapeutic options. Based on early clinical indications of efficacy for the macrocyclic lactone, Ivermectin (IVM), against COVID-19, IVM-based combination treatments were deployed to treat it. Oxygen saturation (SpO2) data were retrospectively analyzed for 34 severe, hypoxic COVID-19 patients all on room air (without supplemental oxygen). The patients, median age 56.5, were treated at clinics or at home … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 44 publications
3
12
0
Order By: Relevance
“…IVM at concentrations of 1–2 µM for the four different viral lineages inhibited HA when added concurrently with spike protein and also reversed HA that had been induced by the prior addition of spike protein. This HA-reversal effect could account for sharp increases observed within 24 h after administration of IVM of pre-treatment depressed SpO2 levels in severe COVID-19 patients, as summarized in Figure 6 below, which reproduces a figure from the most recent of three clinical studies reporting this effect [ 64 ]. In contrast to the sharp, rapid increases in SpO2 levels observed in these studies, moderate and severe COVID-19 patients under standard care typically manifest decreasing SpO2 values in tandem with increasing pulmonary CT abnormalities from the day of onset of disease symptoms through the second week following, as established in several studies that tracked SpO2 values, pulmonary abnormalities, or both [ 65 , 66 , 67 , 68 , 69 , 70 , 71 ].…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…IVM at concentrations of 1–2 µM for the four different viral lineages inhibited HA when added concurrently with spike protein and also reversed HA that had been induced by the prior addition of spike protein. This HA-reversal effect could account for sharp increases observed within 24 h after administration of IVM of pre-treatment depressed SpO2 levels in severe COVID-19 patients, as summarized in Figure 6 below, which reproduces a figure from the most recent of three clinical studies reporting this effect [ 64 ]. In contrast to the sharp, rapid increases in SpO2 levels observed in these studies, moderate and severe COVID-19 patients under standard care typically manifest decreasing SpO2 values in tandem with increasing pulmonary CT abnormalities from the day of onset of disease symptoms through the second week following, as established in several studies that tracked SpO2 values, pulmonary abnormalities, or both [ 65 , 66 , 67 , 68 , 69 , 70 , 71 ].…”
Section: Discussionsupporting
confidence: 54%
“… Mean changes in oxygen saturation (SpO2) for severe COVID-19 patients following treatments including or excluding IVM. Reproduced from Stone et al, 2022 [ 64 ] (CC-BY 4.0). Patients tracked over various time periods from each regimen were those with SpO2 values all recorded on room air, having pre-treatment (day 0) values ≤ 93%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, increase in SPO2 on IVM was magnified in Males (Figure 5). Similar findings of rapid rise in SPO2 on Ivermectin was reported by Stone et al 40 . In 34 patients treated in Zimbabwe, the authors noted a mean increase in SpO2 as a percentage of full normalization to SpO2 = 97% of 55.1% at +12 h and 62.3% at +24 h after the first IVM dose (pairedt-test,p< 0.0000001).…”
Section: Ivermectin and Changes In Arterial Oxygensupporting
confidence: 90%
“…This HA-reversal effect could account for sharp increases observed within 24 hours after administration of IVM of pre-treatment depressed SpO2 levels in severe COVID-19 patients, as summarized in Figure 6 from the most recent of three clinical studies reporting this effect. 62 The inhibition of HA by IVM as reported here parallels the prevention of RBC clumping in Zebrafish embryos by heparan sulfate, a glycosaminoglycan likewise indicated to strongly bind to SARS-CoV-2 spike protein, 49,63 when coinjected with spike protein. 49 It is noteworthy that the scattered RBC clumps observed in this Zebrafish embryo study, as with those observed in the blood of COVID-19 patients, 26-28 are much smaller than the macroscopic-scale HA—clusters of extensively interlaced RBCs—observed in this study.…”
Section: Discussionsupporting
confidence: 65%